Analysis of Nickel(II) in Water Medium using Electrochemical Techniques - Gayatri Citra Dewi; Odetta Levin (Pusat Inovasi Sains, 2023)
Nickel (Ni) is a highly toxic heavy metal because nickel can accumulate and poison aquatic biotic components, therefore it’s levels must be determined with certainty. In this study, nickel metal measurements were made using the cyclic voltammetry method. Several measurement parameters, including voltage range, scan rate, and pH, were tested in this study to improve sensitivity and accuracy. This is done to achieve the best possible measurement conditions. The results show that the best conditions for detecting Ni ions are a voltage range of -0.75 V to -1.00 V, a scan rate of 250 mV/s, and a pH of 3. The validation test produced results in the range of 15 to 40 mM with a correlation coefficient of 0.99, detection and quantitation limits of 274.99 ppm and 916.66 ppm, respectively, and an RSD of 1.10%. As a comparison, Ni content was tested using AAS, and the Ni contents obtained by cyclic voltammetry and AAS methods were 1666.47 and 1676 ppm, respectively.